استعمالات خاصة للقرآن الكريم لبعض المفردات - Abdoul Karim Toure; Mohd Zohdi Mohd Amin; Mesbahul Hoque; Robiatul Adawiyah Mohd @ Amat; Norazman Alias; Zainora Daud; Norzulaili Mohd Ghazali; Muhammad Yusuf Ismail (USIM Press, 2024)
Non-Indexed Publication